PENGARUH PENETAPAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN KONSUMEN PADA PT. PEGADAIAN CABANG PANAM PEKANBARU (STUDI PRODUK TABUNGAN EMAS PT. PEGADAIAN CABANG PANAM PEKANBARU - Oktafania, Nia; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Consumer satisfaction is one of the benchmarks of the success of the marketing strategy used by a company. Setting the right price and good quality of service provided to consumers will be supporting factors that result in customer satisfaction. This strategy is applied by PT. Pegadaian Panam Pekanbaru Branch. This study aims to determine the effect of pricing and service quality on consumer satisfaction at PT. Pegadaian Panam Pekanbaru Branch (Study of Gold Savings Products PT. Pegadaian Panam Pekanbaru Branch). The method used in this research is descriptive and quantitative statistics. The population in this study were all consumers of gold savings products PT. Pegadaian Panam Pekanbaru Branch from 2016- 2020. Samples were taken as many as 100 respondents using accidental sampling technique. Sources of data used in this study came from primary data obtained through the process of distributing questionnaires which were then tested statistically through the SPSS program. The secondary data used are sales data and data on customer realization targets for the Gold Savings product of PT. Pegadaian Panam Pekanbaru Branch from 2016-2020.The analytical method used in this research is simple and multiple linear regression analysis, by going through the validity test and reliability test. In this study the results obtained are that price fixing (X1) has a significant effect on consumer satisfaction (Y), Service Quality (X2) has a significant effect on Consumer Satisfaction (Y) and Pricing (X1) and Service Quality (X2) have a significant effect on Consumer Satisfaction (Y) at PT. Pegadaian Panam Pekanbaru Branch. Keywords: Pricing, Service Quality and Consumer Satisfaction